Efeect Of Hot-Air Drying On Physical Properties And Colour Characteristics Of Beetroot (Beta Vulgaris L.) (Applied Biological Research, 2020)
Beetroot is recognized as health promoting food due to presence of  essential components such as vitamins, minerals, phenolics, carotenoids,  nitrate, ascorbic acids and betalains that promote health. Good quality  beetroot samples (100) were randomly taken and characterized for  physical properties viz., shape, length, width and thickness. Derived  dimensional properties like geometric diameter, equivalent diameter,  arithmetic diameter, sphericity, surface area, aspect ratio, bulk density,  true density, peel thickness, angle of repose and packing coefficient were  alculated. These properties are necessary for designing the equipment for  harvesting, sorting, separating and packing. The mean values of sphericity  and surface area were found to be 0.91 and 79.63 cm2. The average values  of aspect ratio, peel thickness and angle of repose were 0.94, 1.06 mm and  40.67°, respectively. The drying experiments were carried out under three  air temperatures of 40, 50 and 60°C, air velocity of 1.0 m/s beetroot slice  thickness of 2 mm. The colour parameters for colour change of the  materials were quantified by Hunter (Lab) system. These values were also  used to calculate the total colour change, chroma, Hue angle and browning  index. It was observed that L, a, b and chroma were fitted to first order  kinetics model, whereas ∆E and Hue angle followed zero order kinetic  model.
Keywords: Beetroot; browning index; chroma; colour parameters; hot air drying; Hue angle; physical properties